LEUKOCYTE ESTERASE IN ASCITES FLUID FOR DETECTING SPONTANEOUS BACTERIAL PERITONITIS IN LIVER CIRRHOSIS - Mawar Afrida; Ricke Loesnihari; Juwita Sembiring (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2018)
Spontaneous Bacterial Peritonitis (SBP) is a frequent complication in liver cirrhosis with ascites patients. Spontaneous bacterial peritonitis is often without symptoms, so diagnosis is often delayed. Ascites fluid analysis is expensive, while the ascites fluid culture, as the gold standard, takes a long time and is expensive too. Besides, not all hospitals have the facilities to do both tests. Dye strip test that detect leukocyte esterase, that was originally developed to detect the presence of polymorphonuclear cells in the urine was also sensitive and accurate for detecting the presence of polymorphonuclear cells in the ascites fluid. This examination is easy and quick to do and very cheap so that can be used for early detection of SBP. To determine the sensitivity, specificity, Positive Predictive Value (PPV) and Negative Predictive Value (NPV) of dye strip leukocyte esterase test for early detection of SBP in liver cirrhosis with ascites patients were studied. This study used a dye strip leukocyte esterase (Combur10 Test®M) in 28 samples of ascites fluid and compared with the results of ascites fluid culture. The ability of the leukocyte esterase test as a diagnostic test was very good at a cut-off +2 with 94.1% specificity, 63.6% sensitivity, 35% PPV and 80% NPV. Examination leukocyte esterase in the ascites fluid could be used for early detection of SBP in liver cirrhosis with ascites patients and could help to exclude SBP..